2017
DOI: 10.4309/jgi.v0i34.3962
|View full text |Cite
|
Sign up to set email alerts
|

Gambling and Video Game Playing Among Youth

Abstract: Gambling and video game playing represent two leisure activities in which adolescents and young adults participate. There are psychological and behavioural parallels between some forms of gambling (e.g., slot machines, video lottery terminals, electronic gambling machines) and some types of video games (e.g., arcade games). Both activities operate on behavioural principles of variable reinforcement schedules in order to reward and prolong play and use exciting and stimulating sound and light effects within gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 58 publications
2
17
0
3
Order By: Relevance
“…Their results suggested that 37.2% of their participants had experienced the co-occurrence of problematic work, 36.6% had experienced problematic eating behaviors (i.e., eating too little or too much), 14.1% had experienced problematic sex (i.e., excessive sexual behavior), and 12.3% had experienced problematic gambling. The latter finding was in line with a study by McBride et al [85], which reported that 11.4% of disordered gamers within in their sample experienced problem gambling, and which is consistent within the wider literature [100,101]. Finally, a study by Ivory et al [83] on US college students (n = 533) suggested that gaming was not significantly associated with nicotine or substance use.…”
Section: Proxy Indicators Of Prevalence Of Gaming Disorder and Other supporting
confidence: 87%
See 3 more Smart Citations
“…Their results suggested that 37.2% of their participants had experienced the co-occurrence of problematic work, 36.6% had experienced problematic eating behaviors (i.e., eating too little or too much), 14.1% had experienced problematic sex (i.e., excessive sexual behavior), and 12.3% had experienced problematic gambling. The latter finding was in line with a study by McBride et al [85], which reported that 11.4% of disordered gamers within in their sample experienced problem gambling, and which is consistent within the wider literature [100,101]. Finally, a study by Ivory et al [83] on US college students (n = 533) suggested that gaming was not significantly associated with nicotine or substance use.…”
Section: Proxy Indicators Of Prevalence Of Gaming Disorder and Other supporting
confidence: 87%
“…More specifically, while gaming, between 23.3-74.2% of gamers consumed caffeine [82,86], 21.7-25.3% smoked cigarettes [82,86], 41.2-44.6% smoked cannabis [28,82], 21.3-40.4% consumed alcohol [82,86], and 14.5% consumed illicit substances [86]. In regard to problematic and disordered behavior, the findings suggested that problematic gambling [85], problematic shopping, problematic sex, and problematic work [84] were associated with disordered gaming, while disordered exercise was not related [29,83].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because there are many structural similarities between gambling, especially electronic gambling machines, and electronic gaming (e.g. the use of variable reinforcement schedules to reward and prolong play, sound and light effects) , and both activities have similar negative effects associated with excessive play (e.g. poor academic performance, moodiness, interpersonal conflicts) , there may be reasons to believe that the four types of motivations identified among gamblers are also relevant to gaming.…”
Section: Introductionmentioning
confidence: 99%